„Mors est a vita discedere”. Teologiczna koncepcja śmierci w nauczaniu Orygenesa - Duda, Jerzy (Verbum Vitae, 2013)
Origen from Alexandria (†253), one of the most eminent early Christian writers, is the pioneer of a very interesting theological conception of death. It is connected with his general soteriology doctrine. In the Christocentric theology of Origen, not so much death but Life itself, the synonym of the Savior, determines the principle of his interests, scientific research, and teaching. Death is a departure from Life. It separates us from God and connects with the reality destined to be doomed. The allegorical method used by the Alexandrian enabled him to identify the expression “death” with the Devil. Origen created the so-called doctrine of three kinds of death. First of them is the physical death. It is a consequence of the “paradise sin” and refers to all people. According to the classical definition, it is a separation of the soul from the body. The second one is the death by sin which leads to annihilation. The third one is the death for sin which means eternal happiness in heaven and coming back to the origins of life together with Christ. Origen hopes that at the end of times death will be conquered as the „last enemy”, and all human beings, submitted to it until now, will be purified and will return to the original unity with the Lord.